Clustering Analysis of the Multi-Microbial Consortium by Lactobacillus Species Against Vaginal Dysbiosis Among Ecuadorian Women - Pacha-Herrera, David; Erazo-Garcia, Maria P.; Cueva, Darío F.; Orellana, Miguel; Borja-Serrano, Pamela; Arboleda, Camila; Tejera, Eduardo; Machado, António (Frontiers in Cellular and Infection Microbiology, 2022)
The vaginal microbiota plays vital protection in women. This probiotic activity is caused not only by individual Lactobacillus species but also by its multi-microbial interaction. However, the probiotic activity promoted by multi-microbial consortia is still unknown. The aim of this study was the individual and collective analysis on the prevalence of five vaginal lactobacilli (Lactobacillus iners, Lactobacillus crispatus, Lactobacillus gasseri, Lactobacillus jensenii, and Lactobacillus acidophilus) among healthy women and women with bacterial vaginosis (BV) or aerobic vaginitis (AV). PCR assays were realized on 436 vaginal samples from a previous study. Chi-square, univariable, and multivariable logistic regression analyses with the Benjamini–Hochberg adjustment evaluated associations between these lactobacilli and vaginal microbiota. Multi-microbial clustering model was also realized through Ward’s Minimum Variance Clustering Method with Euclidean squared distance for hierarchical clustering to determine the probiotic relationship between lactobacilli and vaginal dysbiosis. Concerning the individual effect, L. acidophilus, L. jensenii, and L. crispatus showed the highest normalized importance values against vaginal dysbiosis (100%, 79.3%, and 74.8%, respectively). However, only L. acidophilus and L. jensenii exhibited statistical values (p = 0.035 and p = 0.050, respectively). L. acidophilus showed a significant prevalence on healthy microbiota against both dysbioses (BV, p = 0.041; and AV, p = 0.045). L. jensenii only demonstrated significant protection against AV (p = 0.012). Finally, our results evidenced a strong multi-microbial consortium by L. iners, L. jensenii, L. gasseri, and L. acidophilus against AV (p = 0.020) and BV (p = 0.009), lacking protection in the absence of L. gasseri and L. acidophilus.